Formação de professores: o descrever como instrumento no processo de desenvolvimento da reflexão crítica do professor nas aulas de língua inglesa na escola pública - Cruz, Danieide Rodrigues da (2013)
This study aims to investigate the action of description as a tool for guiding the development process of critical reflection of English teachers in public schools, and more specifically understand and analyze how the action of description can assist in conducting this critical reflection. For that, we analyzed and compared three versions of the action of description, elaborated during Reflexão na/sobre a ação, in the course Práticas Reflexivas e ensino-aprendizagem de Inglês na escola pública. The study is done through action research, with interpretive view, based on the performance of an English teacher in public school. This research is theoretically based on the following authors: Liberali (2008), with fundamental questions about the teacher’s formation; Perrenoud (2002), Romero (2009); Magalhães (2004), Schön (2000); Celani (2004); Schön (1987), Gomez (1992), Freeman (1992), apud Shimoura and Fidalgo (2007), Vygotsky (1934), cited Liberali (2008); Leontiev (1972), Bakhtin (1979), apud Liberali (2008); Kerbrat - Orecchioni (2006), among others. The results of the research reveal the process of reconstruction of the action of description and also show how this action became an important instrument for the conduct of critical reflection